Changes in poly(a)+ RNA during male meiosis in Lilium. - Porter, E; Parry, D; Dickinson, H (1983)
Levels of poly(A)+ RNA have been investigated at each stage of male meiosis in Lilium (var. Firecracker). Two methods were employed in this work: in one extracts from labelled meiocytes were passed through oligo(dT) columns, while in the other the specific probe [3H]poly(U) was hybridized in situ with resin-embedded sections of pollen mother cells. The label contained in the eluate from the oligo(dT) columns was measured by liquid scintillation, and the quantity of [3H]-poly(U) hybridized was determined by statistical analysis of light microscopic autoradiographs. Both techniques revealed a dramatic decline in detectable poly(A)+ RNA during prophase. Lowest levels are reached in the pachytene stage, following which a gradual restoration of this species of RNA takes place in both nucleus and cytoplasm. The data presented here provide no clear indication as to whether this fall in RNA levels is caused by the action of novel enzymes specific to the meiotic prophase, by a cessation of synthesis and the activity of normal turnover processes, or by a combination of the two. Although there is some evidence from the [3H]poly(U) hybridization study that a small peak of poly(A)+ RNA synthesis may take place in leptotene, both methods indicate that there is a very low of poly(A)+ RNA synthesis throughout prophase. The presence of poly(A)+ RNA was not detected in either the accessory nucleoli or the cytoplasmic nucleoloids that characterize the nucleus and cytoplasm of these cells. These events are considered in terms of the juncture at which they occur in the plant life-cycle.